The Importance of Information Technology Project Management Management Towards the Success of a Company - Dymas Kharafi Sugara; Galuh Tresna Murti; Shendy Tiodor Lina Sitanggang; Yolla Eka Saputri (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
The presentation of the results in the worksheet of this paper explains the extent to which information technology project management is important to the company. The method used in its preparation is descriptive qualitative method. This method is carried out by examining and determining validity and analyzing from various perspectives. The preparation of this paper worksheet uses a variety of different data sources. The results found indicate that the importance of managing an information technology project will affect the success or failure of a company. information